The role of digital communication tools in increasing occupational health and safety awareness - Handayani, Hanifah (Jurnal Konseling dan Pendidikan, 2025)
Occupational Health and Safety (OHS) is a critical aspect of workplace management, ensuring employee well-being and reducing occupational hazards. In recent years, digital communication tools have played a transformative role in enhancing OHS awareness through real-time information sharing, interactive training, and automated hazard detection. This study employs a qualitative research approach using a literature review and library research method to analyze the effectiveness of digital platforms—such as e-learning systems, virtual reality (VR) training, social media, mobile applications, and artificial intelligence (AI)—in promoting workplace safety. The findings indicate that VR-based simulations and AI-driven safety analytics significantly enhance employee training effectiveness and hazard prediction. Additionally, social media and mobile applications facilitate instant safety communication, enabling employees to report incidents and receive timely updates. However, challenges such as digital illiteracy, misinformation, data privacy concerns, and high implementation costs persist, particularly for small and medium-sized enterprises (SMEs). The study highlights the importance of balancing technology with human oversight to ensure the ethical and practical application of digital OHS tools. Future research should explore the long-term impact of digital safety interventions on behavioral change and workplace accident reduction. This study contributes to the growing discourse on digital transformation in occupational safety, providing insights for organizations, policymakers, and researchers on optimizing digital communication tools for OHS improvements.